Conflits Fonciers Intercommunautaires Et Fracture Sociale Dans Les Régions Du Guémon Et Du Cavally À L’ouest De La Côte d’Ivoire - François, Kouassi N’goran; Anselme, N’drin Beugré (European Scientific Journal, ESJ, 2016)
The armed conflict that ravaged Côte d’Ivoire after the post-election crisis in november 2010 was sparked by several factors (land disputes, armed uprising of september 2002, tribal militias conquest of state power). In the regions of Guémon and Cavally that formed the epicenter of the war, intercommunal land disputes were instrumental in the outbreak of the war. These tensions between peasants have long caused confusion in the far west forest and contributed in part to the social division between indigenous and migrant communities. This qualitative study based on the phenomenological approach and firstly analyses the dynamics of these communal land disputes before the post-election crisis of 2010. Then, it situates the impact of these conflicts in the social division between communities.